Special issue on Statistical Modelling in Finance Conference 2006 (Temple University) - Elyasiani, Elyas; Thavaneswaran, A.; Singh, Jagbir, Dr (Journal of risk finance, 2006)
This e-book contains papers from the 2006 Statistical Modelling in Finance conference. Using the historical hurricane forecasts of Dr. William M. Gray, the editorial identifies the problem of using "black-box" methods in catastrophe forecasting, and emphasises the value of independent peer review.